Case report: Single infusion of combined anti-CD20 and anti-CD38 monoclonal antibodies in pediatric refractory lupus nephritis - Chiarenza, Decimo Silvio; Mancini, Raul; Bigatti, Carolina; Caridi, Gianluca; Consolaro, Alessandro; Natoli, Valentina; Mortari, Gabriele; Kajana, Xhuliana; Lugani, Francesca; Gattorno, Marco; Ghiggeri, Gian Marco; La Porta, Edoardo; et al. (Frontiers in Immunology, 2025)
Lupus nephritis (LN), present in 30%–50% of systemic lupus erythematosus (SLE) patients, often necessitates standard immunosuppressive therapy (glucocorticoids, MMF, CYC) as suggested by the European League Against Rheumatism/European Renal Association–European Dialysis and Transplant Association (EULAR/ERA-EDTA) and Kidney Disease Improving Global Outcomes (KDIGO) guidelines. However, a subset of subjects remains refractory. Recent findings suggested the efficacy of targeting CD38-long-lived plasma cells in LN and SLE refractory to standard treatment. However, previous experiences were limited to adult patients and described different therapeutical schemes based on daratumumab, with the addition or absence of belimumab. Moreover, the minimal effective dose of daratumumab has yet to be fully defined. In this report, we describe two cases of juvenile-onset refractory LN/SLE successfully managed with a combination of a single infusion of rituximab (targeting CD20 on B cells) and daratumumab (targeting CD38 on long-lived plasma cells), unlike prior regimens requiring prolonged daratumumab infusions. Our approach was safe and effective and may potentially reduce adverse effects and costs, providing a novel therapeutic option for juvenile refractory LN.